(untitled) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
Digital training in rural communities plays a crucial role in enhancing information technology literacy and community empowerment. This study aims to evaluate the effectiveness of a digital training program implemented in Pugu Village, Air Hangat Barat Subdistrict, Kerinci Regency, which focuses on basic computer skills, internet access and usage, and digital applications in daily life. The research method used is a combination of lectures and practical assessments for training participants. The results show that digital training significantly improves participants’ understanding and skills in information technology. Furthermore, the program also increases community participation in various information and communication technology (ICT) activities and opens up new economic opportunities for the community through small-scale digital-based businesses. This study emphasizes the importance of digital training programs as a strategic step to reduce the digital divide and strengthen the capacity of rural communities in facing technological advancements.